2021
DOI: 10.3390/biology10010048
|View full text |Cite
|
Sign up to set email alerts
|

Force Generation on the Hallux Is More Affected by the Ankle Joint Angle than the Lesser Toes: An In Vivo Human Study

Abstract: The structure of the first toe is independent of that of the other toes, while the functional difference remains unclear. The purpose of this study was to investigate the difference in the force generation characteristics between the plantar-flexion of the first and second–fifth metatarsophalangeal joints (MTPJs) by comparing the maximal voluntary plantar-flexion torques (MVC torque) at different MTPJs and ankle positions. The MVC torques of the first and second–fifth MTPJs were measured at 0°, 15°, 30°, and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In all TFS measurements, the angle-adjustable sensor plate was placed at 45° of dorsi exion at the MTP joint, in accordance with previous studies 13,14 . Previous reports have shown that the highest TFS values were determined at 45° of dorsi exion at the MTP joint and 90° of dorsi exion at the ankle joint angles in all cases when TFS was produced by all toes 1 , the great toe, and lesser toes 17 . To avoid extraneous movements, the ankle and forefoot were xed on the ground of the device using Velcro straps.…”
Section: Measurement Of Tfsmentioning
confidence: 54%
“…In all TFS measurements, the angle-adjustable sensor plate was placed at 45° of dorsi exion at the MTP joint, in accordance with previous studies 13,14 . Previous reports have shown that the highest TFS values were determined at 45° of dorsi exion at the MTP joint and 90° of dorsi exion at the ankle joint angles in all cases when TFS was produced by all toes 1 , the great toe, and lesser toes 17 . To avoid extraneous movements, the ankle and forefoot were xed on the ground of the device using Velcro straps.…”
Section: Measurement Of Tfsmentioning
confidence: 54%
“…The dysfunction of the aforesaid structure may trigger a sequence of events and affect the Achilles tendon, calf muscles, the back part of the thigh (hamstrings), and even the lower parts of the spine. According to the latest research [ 26 ], force generation on the hallux is more affected by the ankle joint angle than the lesser toes. A similar situation can be observed as regards the hallux valgus, related to the deformation of the spine, positions of the lower limbs and the range of movements in the ankle [ 27 ].…”
Section: Discussionmentioning
confidence: 99%